A study to compare acceptability, safety and continuation rates of combined hormonal pill and centchroman as post abortion contraceptives - Miuli, Inlo; Dewan, Rupali; Agarwal, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Centchroman a non-steroidal selective estrogen receptor modifier (SERM). It is highly effective contraceptive which is devoid of side effects of COCs and there is prompt return of fertility upon discontinuation. Data in terms of its acceptability and continuation rates is limited when compared to combined oral contraceptive (COC). Therefore, the study was planned to study the acceptability, efficacy and continuation rates of centchroman and compare it with the combined oral contraceptives. Methods: The study was a prospective interventional comparative randomized study carried out in the department of obstetrics and gynecology VMMC and SJH, New Delhi, for a period of 18 months from November 2018 to April 2019. Results: A total of 945 women were screened and finally 240 women who met the criteria were recruited in 2 study groups of 120 women each. Majority were in the age group 18-28 years in either groups. Patients were followed up at 2nd week and then at 1st, 3rd, 6th and 12th months after initiation of the OCP with no loss to follow up. The pearl index in this study was 0.83 for ormeloxifene. The study showed statistically significant differences with higher level of satisfaction reported with 77.5% in the ormeloxifene compared to 65% of COCs. The continuation rates for ormeloxifene and COC users were in decreasing trend with increase in duration. No untoward events were reported with either formulation. Conclusions: Both the hormonal, combined hormonal contraceptive [combined oral contraceptive (COC), MALA-N] and the non-hormonal, centchroman (ormeloxifene) oral contraceptive pills are safe, effective, well tolerated and not associated with adverse outcomes when used immediately after abortion. Continuation rates of the pills in both the groups decrease in trend with time.